Boosting electrochemical water oxidation through replacement of Oh Co sites in cobalt oxide spinel with manganese. Issue 57 (30th June 2017) - Menezes, Prashanth W.; Indra, Arindam; Gutkin, Vitaly; Driess, Matthias
Abstract : Effect of substitution in the spinel lattice, structure–activity relation and nature of active species involved during oxygen evolution reaction were uncovered in the manganese cobalt oxide (MCO). Abstract : The strikingly high catalytic performance and stability of manganese substituted cobalt oxide spinel (Mn x Co3− x O4 ) over pristine cobalt oxide spinel (Co3 O4 ) for the alkaline electrochemical water oxidation is reported. The different role of cations could be uncovered along with the detection of drastic surface-structural changes during the catalysis using spectroscopic and microscopic methods.